Usulan Perancangan Ulang Tata Letak Fasilitas Berbasis ALDEP (Studi Kasus Pada Gema Frozen) - Maulana Anam, Muhammad Akbar; Muflihah, Nur; Minto (INVANTRI (Inovasi Dan Pengelolaan Industri), 2024)
Gema Frozen is a company engaged in the distributor of frozen food products. The problems that occur at Gema Frozen are the ineffective distribution process and the lack of attention to layout in the company, especially in the flow of goods storage. This study aims to create a structured layout that increases the effectiveness of material handling and optimization of material transfer distances based on ALDEP (Automated layout Design Program) in order to create good and comfortable conditions in the company environment. Obtained the value of the results of the calculation of ARC and TCR in the office of 3, loading in by 7, incoming goods by 8, cool storage by 12, Transit Area 11, outcoming goods 7, loading out 6, Terrace 0. The highest value of TCR is in cold storage which reaches 12, this ranking indicates that the high level of need for cool storage. After analyzing the redesign with the ALDEP method, the total distance obtained is 43.1 with several changes in each department, namely loading in and loading out which were originally side by side are now separated to be more efficient, the office is brought closer to between incoming goods, outcoming goods and cool storage Therefore, there is a distance savings in the distribution process flow of 6.68%.